Prognostic implication and immunotherapy response prediction of a ubiquitination-related gene signature in breast cancer - Guo, Yangyang; Chen, Qiaoqiao; Zhang, Yingjue; Cheng, Xu; Cen, Kenan; Dai, Ying; Mai, Yifeng; Hong, Kai (Frontiers in Genetics, 2023)
Breast cancer (BC) is one of the most common tumor types and has poor outcomes. In this study, a ubiquitination-related prognostic autograph was constructed, and its association with immunotherapy response in BC was explored. Ubiquitination-related genes were obtained from the Molecular Signatures Database, and patients with BC were categorized into two clusters. A ubiquitination-related gene signature was obtained via least absolute shrinkage and selection operator Cox regression investigation. TCN1, DIRAS3, and IZUMO4 significantly influenced BC. Patients in the high-risk group had inferior survival than those in the low-risk group. Univariate and multivariate Cox regression analyses revealed that the risk signature was an independent prognostic factor for BC. Gene set enrichment analysis suggested that the high-risk group was enriched in cell cycle and DNA replication pathways. The risk score was positively linked to the tumor microenvironment score and negatively correlated with immunotherapy response. The IC50 values of rapamycin were higher in the low-risk group, whereas those of axitinib, AZD6244, erlotinib, GDC0941, GSK650394, GSK269962A, lapatinib, and PD0325901 were higher in the high-risk group. Therefore, the ubiquitination-related signature is considered a promising tool in the immunotherapy response in BC.